Pengembangan Potensi Ekonomi Desa Melalui Wisata Embung Pintar - Irfan, Muhammad; Mokhtar, Ali; Pringga P, Okta (Berdikari: Jurnal Inovasi dan Penerapan Ipteks, 2020)
The existence of embung (small lake) as a reservoir in a farm area becomes very important for the sustainable supply of irrigation water. So is the existence of embung in Jambesari Village, Poncokusumo, Malang. Besides the main function as irrigation water source, embung can be developed into a tourism object. Based on that potential, embung in Jambesari Village needs to be developed into Embung Pintar Tourism. In order to achieve the goal, area management by adding facilities around embung is necessary to be done, both physically and non-physically with internet as its main facility. This program was conducted by taking the steps of identification and assessment, planning, planning implementation, supervision and evaluation for the sustainable action. This Partnership Program succeeded to increase the performance of Jambesari Village through Embung Pintar Tourism. The attractiveness of embung tourism was shown by the addition of physical facilities, such as gazebo and floating karamba supported by the main facility of 5 -hour unlimited internet access as the characteristic of Embung Pintar. Embung Pintar Tourism was managed with good management based on embung tourism income and the improvement of society economy become the sustainable guarantee.